2020
DOI: 10.4187/respcare.07955
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spontaneous Breathing Trials in Cardiorespiratory Stability of Preterm Infants

Abstract: BACKGROUND: A spontaneous breathing trial (SBT) is commonly used to determine extubation readiness in patients receiving mechanical ventilation. However, the physiological impact of such a trial in preterm infants has not been well described. This study aimed to investigate the effects of a 3-min SBT on the cardiorespiratory stability of these infants. METHODS: A retrospective analysis of prospectively collected data was done for infants < 37 weeks gestational age who were extubated after a successful 3-min SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“… 26 In that study, however, the EMG was measured during invasive ventilatory support, which could have suppressed the respiratory drive and hence any difference in diaphragmatic function would not have been observed. The use of a spontaneous breathing trial (SBT) has been reported to be 97% sensitive but of low (40%) specificity in predicting readiness for extubation, 27 making use of an SBT alone not routinely recommended in preterm infants given the inaccuracy in predicting extubation failures 28 , 29 along with reports of clinical instability. We thus hypothesised that a combined measurement of the Edi during an SBT would increase the specificity of the assessment.…”
Section: Introductionmentioning
confidence: 99%
“… 26 In that study, however, the EMG was measured during invasive ventilatory support, which could have suppressed the respiratory drive and hence any difference in diaphragmatic function would not have been observed. The use of a spontaneous breathing trial (SBT) has been reported to be 97% sensitive but of low (40%) specificity in predicting readiness for extubation, 27 making use of an SBT alone not routinely recommended in preterm infants given the inaccuracy in predicting extubation failures 28 , 29 along with reports of clinical instability. We thus hypothesised that a combined measurement of the Edi during an SBT would increase the specificity of the assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In another retrospective study, the infants who failed extubation did not increase breathing frequency or work of breathing statistically significantly following a 3-min SBT compared to those infants with a successful extubation ( 17 ). The inability to compensate for the transiently increased cardiorespiratory load during a trial might be an indicator of cardiorespiratory function deterioration, which can lead to potentially catastrophic (sometimes fatal) consequences ( 18 20 ). Therefore, a reasonable assumption is that the infants required early reintubation (within 72 h) deteriorated clinically after initial extubation as a direct result of the removal of the ventilatory support provided during mechanical ventilation, such as atelectasis, apnea, and hemodynamic instability ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to these studies, SBT has high sensitivity and positive predictive value but low specificity and negative predictive value in evaluating the neonates' readiness for extubation. Therefore, despite its low costs and availability, SBT cannot be considered a test with accurate results in assessing the neonates' readiness for extubation [24,[29][30][31]. The ability of SBT to predict success may be due to the increased resistance and dead space of the endotracheal tubes in small premature on CPAP, which increases the work of breathing.…”
Section: Spontaneous Breathing Trialmentioning
confidence: 99%